Mortality in HIV infection is independently predicted by host iron status and SLC11A1 and HP genotypes, with new evidence of a gene-nutrient interaction. - McDermid, J; van der Loeff, M; Jaye, A; Hennig, B; Bates, C; Todd, J; Sirugo, G; Hill, A; Whittle, H; Prentice, A (2009)
BACKGROUND: Iron-related genes and iron status may independently contribute to variable HIV outcomes. The nature of the biologically plausible gene-nutrient interaction remains unknown. OBJECTIVES: The objectives were to investigate whether iron-related genotypes and clinically abnormal iron status independently predict mortality in HIV and whether a gene-nutrient interaction exists. DESIGN: Baseline plasma, DNA, and clinical data were obtained from 1362 HIV-seropositive Gambian adults followed for 11.5 y to ascertain all-cause mortality. Iron status was estimated on the basis of plasma iron, soluble transferrin receptor (sTfR), ferritin, transferrin, transferrin index, and log(sTfR/ferritin). One haptoglobin (HP) and 5 SLC11A1 (NRAMP1) polymorphisms were genotyped. RESULTS: SLC11A1-SLC3 and CAAA polymorphisms were the best independent genetic predictors of mortality [adjusted mortality rate ratio (95% CI)]: SLC3:G/C = 0.59 (95% CI: 0.45, 0.85), CAAA:del/ins = 1.51 (95% CI: 1.10, 2.07). In an adjusted model that included all polymorphisms, SLC1:199/199, SLC1:other/other, SLC6a:A/A, and CAAA:del/ins were associated with significantly greater mortality, whereas Hp 2-1 and SLC3:G/C were protective. In unadjusted analyses, all biomarker concentrations were significantly associated with mortality. In an extension of previous findings, both low and elevated iron states were associated with mortality, but the nature of the risk was variable, with linear, inversely linear, and U-shaped associations depending on the biomarker. Mortality was significantly lower in HIV-2 than in HIV-1 infection in the presence of abnormal (low or elevated) iron status. A gene-iron interaction was detected (likelihood-ratio test P = 0.018); however, subject numbers restricted category-specific interpretation. CONCLUSIONS: Iron-related genes, iron status, and their interaction predict mortality in HIV. These findings illustrate the complexity and uncertainty surrounding best practice for managing abnormal iron status and anemia during HIV infection and in regions with a high risk of infection.